2002
DOI: 10.1097/00000539-200203000-00010
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Universal Leukodepletion of Packed Red Blood Cells on Postoperative Infections in High-Risk Patients Undergoing Abdominal Aortic Surgery

Abstract: We evaluated the influence of leukocyte reduction by filtration of packed red blood cells (RBC) on postoperative infections and adverse outcomes in patients undergoing elective major aortic surgery by comparing two epochs with and without filtration. Data from this study suggest that the effect of using filtered RBC on postoperative infections is not of obvious importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 46 publications
2
56
0
Order By: Relevance
“…In different studies, LR has been shown to have no effect on infection rates in colorectal surgery [32], elective orthopedic surgery [30], elective cardiac surgery [30,33], or elective major aortic surgery [25]. In-house mortality and LOS have also been shown to be equivalent in a general inpatient population receiving LR versus non-LR blood [34].…”
Section: Discussionmentioning
confidence: 99%
“…In different studies, LR has been shown to have no effect on infection rates in colorectal surgery [32], elective orthopedic surgery [30], elective cardiac surgery [30,33], or elective major aortic surgery [25]. In-house mortality and LOS have also been shown to be equivalent in a general inpatient population receiving LR versus non-LR blood [34].…”
Section: Discussionmentioning
confidence: 99%
“…No clear statement can be made whether universal leukoreduction was indeed associated with any clinical advantage with regard of overall mortality rate, infection rate, or cancer recurrence [74], [75], [76], [77], [78].…”
Section: Clinical Studies On Transfusion-related Immunomodulationmentioning
confidence: 99%
“…However, the two Canadian studies 29,30 could not attribute any improved outcomes observed post-universal WBC reduction to the introduction of the intervention per se. 31 In fact, other observational, before-and-after studies that made similar comparisons between patients transfused before or after implementation of universal WBC reduction in France 32 or England 33 reached different conclusions, and the findings of Hébert et al 29 and Fergusson et al 30 contrast sharply with the results of the RCT of Dzik et al 34 that assessed the benefits of universal WBC reduction in a prospective and experimental manner. Thus, the two Canadian studies 29,30 generated evidence of no harm that is valuable for countries that have already implemented universal WBC reduction.…”
Section: Summary and Discussionmentioning
confidence: 97%